THE ROUTE OF RETURN OF THE TORGUTS TO CHINA: BASED ON MATERIALS OF XIYU WENJIAN LU BY QISHIYI (Journal of Oriental Studies, 2023)
The article examines and analyzes the materials on the history of the migration of Torguts, in 1771, from the Lower Volga region to China, which are contained in the sixth chapter of Xiyu wenjian lu (西域闻见录 ‘Record of Things Seen and Heard in the Western Regions’) by Qishiyi. The aim of the study is to study, analyze and introduce into scientific circulation a new translation of important and valuable material from Xiyu wenjian lu on the history of the migration of most of the Kalmyks from the Volga steppes. This Chinese written source is well known to Russian researchers since translations into Russian of the extract on the history of the Torguts (S. V. Lipovtsov) and the entire text (N. Ya. Bichurin) were published in 1820 and 1829. However, it should be emphasized that these two translations have numerous omissions and errors, and also, the first edition has a significantly distorted meaning of the source’s text.The research applied generalizing and comparative methods of research, as well as historical-chronological and comparative-critical analysis, to study materials relevant to our research theme. A new commented translation of an extract from the sixth chapter of Xiyu wenjian lu by Qishiyi titled ‘The Brief Description of Return to Allegiance of the Torguts’ is being introduced into scientific discourse. The historical toponyms mentioned by Qishiyi have been identified, and explanations were given. The authors, relying on information from the source, determined the most probable route for the movement of the Torguts through the territory of the Kazakh steppes.The article was prepared as part of a scientific project funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan, grant project no. AP09259919.Keywords: Route of Torguts, Qishiyi, Xiyu wenjian lu, Ubashi, Qing Empire, historical toponyms, Kazakh khans